Model Pembelajaran Problem Based Learning dapat Meningkatkan Motivasi Belajar Membaca pada Mata Pelajaran Bahasa Indonesia Kelas 1 - Irza Isnaini Marfu’ah (Universitas Sebelas Maret, 2022)
The aim of this research is to increase students' reading motivation in Indonesian language subjects in grade 1 elementary schools using the Problem Based Learning model. The research carried out was Class Action Research (PTK) in two cycles, with each cycle consisting of two meetings. The stages of each cycle are planning, implementation, observation and reflection. At each meeting, a post test is carried out to determine the progress of students. In cycle I, 82% of students completed the post test. In cycle II, 94% of students completed the post test. This shows that the Problem Based Learning learning model can increase students' reading motivation, especially in Class 1 Indonesian Language subjects at SD Al Islam 4 Kadipiro Surakarta.